The Influence of Business Ethics and Viral Marketing on Trust Consumers Through Brand Image as A Mediating Variable - Putri, Amelia; Sunarya, Erry; Suwiryo, Darmo H. (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The problem phenomenon addressed in this study is the low level of consumer trust in MS Glow skincare products compared to its competitors. This research aims to examine the influence of business ethics and viral marketing on consumer trust with brand image as a mediating variable. The research method used is quantitative with a causal descriptive approach. The population of the study consists of female students in Sukabumi who are MS Glow users, with a sampling technique of probability sampling using proportionate stratified random sampling and a sample size of 391 respondents. The data analysis technique used is Structural Equation Modeling (SEM). The results of the study indicate that business ethics does not have a significant direct effect on consumer trust but has a significant positive effect on brand image. Additionally, brand image has a significant effect on consumer trust. Viral marketing also has a significant impact on both brand image and consumer trust. Mediation results show that brand image fully mediates the relationship between business ethics and consumer trust, as well as between viral marketing and consumer trust. Therefore, brand image plays a crucial role in enhancing consumer trust in MS Glow products.